Evaluating the Capability of Epipremnum aureum and Its Associated Phylloplane Microbiome to Capture Indoor Particulate Matter Bound Lead - Much, Diego Gabriel (2025)
In this study we evaluated over a 1-year period, the ability of Epipremnum aureum leavesto collect particulate matter (PM)-bound Pb from an indoor environment. Using IlluminaMiSeq, we investigated the changes in the phylloplane microbiome connected with theaccumulation of this pollutant. Plants were placed in a shooting room, where PM releasefrom each shot was recorded, along with PM2.5 and PM10 sequestration and leaf elementenrichment by ICP. Additionally, black carbon (BC) sequestration was determined, andSEM-EDX was performed on leaves after 12 months of exposure. Our results indicated thatambient air pollution shapes microbial leaf communities by affecting their diversity. Atthe order level, Pseudomonadales, along with Micrococcales, appeared (at a low relativeabundance) after exposure to indoor PM-bound Pb air pollution. This study provides aunique comparison of Epipremnum aureum air filtration performance between a standardoffice environment and a firearm shooting range. The air filtration approach holds promisefor reducing indoor air pollution, but more knowledge about the underlying mechanismssupporting genera capable of coping with airborne pollutants is still required.